Unpacking language teacher beliefs, agency, and resilience in the complex, unprecedented time: A mixed-method study - Gao, Yang; Qin, Lili; Gu, Qiyi (Frontiers in Psychology, 2022)
We conducted this mixed-method study by focusing on the influx relationship among teacher beliefs, agency, and resilience during the pandemic and exploring the relationships and tensions among these constructs or capacities. Specifically, we surveyed 93 language teachers across seven different regions in China and collected their perceptions and beliefs about challenges and solutions during the first wave of the pandemic. In a further step, we interviewed six participants, analyzed the transcripts of the interviews, and then explored how their agency and resilience emerged and developed during the pandemic. From the quantitative statistics, we reported teacher beliefs about emotional, physical, mentoring, and support challenges in emergency remote teaching and their adopted strategies to handle these challenges during the pandemic. We also reported significant correlations among different perceived challenges and solutions. From the qualitative analysis, we found that language teacher beliefs, agency, and resilience co-evolved from intrapersonal and interpersonal reflections through temporal and contextual affordances. Drawing from the sociocultural theory, we contributed a theoretical framework for studying language teacher beliefs, agency, and resilience. We discussed our findings around the global traits that language teachers are required to develop in the increasingly complex world and also offered implications for language teacher education programs.